2020
DOI: 10.3390/su12052020
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Indoor Environment Assessment through Architectural Analysis for the Design of Efficient Schools

Abstract: Optimization of environmental performance is one of the standards to be achieved towards designing sustainable buildings. Many researchers are focusing on zero emission building; however, it is essential that the indoor environment favors the performance of the building purpose. Empirical research has demonstrated the influence of architectural space variables on student performance, but they have not focused on holistic studies that compare how space influences different academic performance, such as Mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The metric should give more weight to the radon concentration due to the health risk it poses. The weight the metric assigns to the other variables could be determined by testing to obtain values close to the ones considered optimal in the literature [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metric should give more weight to the radon concentration due to the health risk it poses. The weight the metric assigns to the other variables could be determined by testing to obtain values close to the ones considered optimal in the literature [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It includes previously mentioned aspects such as air quality, comfortable temperature, noise pollution, all of those aspects related to this study. Research has shown that IEQ has a relevant impact on the performance of those who occupy the space [28][29][30]. Besides the before-mentioned health, economic and environmental impacts, poor IEQ in buildings makes its occupants less happy and less productive, specifically in workplaces [31].…”
Section: Introductionmentioning
confidence: 99%
“…The influences of social interactions and the peer effect have been analyzed in recent studies on educational buildings that include disruptive and attractive methodologies such as gamification [27,28]. In addition, classroom design can foster interaction and collaboration among peers, affecting teaching methodology and improving learning [29].…”
Section: Peer Effect and Active Methodologies In Higher Educationmentioning
confidence: 99%
“…It includes aspects such as air quality, comfortable temperature, air quality and adequate humidity levels. Research has shown that IEQ has a relevant impact in the performance of those who occupy the space [17][18][19]. IEQ is a value that indicates to what extent the energy used for the construction and use of a building is useful or efficient.…”
Section: Resourcesmentioning
confidence: 99%